Case report: Altered pre-mRNA splicing caused by intronic variant c.1499 + 1G > A in the SLC4A4 gene - Liu, Yan; Sheng, Wenchao; Wu, Jinying; Zheng, Jie; Zhi, Xiufang; Zhang, Shuyue; Gu, Chunyu; Guo, Detong; Wang, Wenhong (Frontiers in Pediatrics, 2022)
Proximal renal tubular acidosis with ocular abnormalities is an autosomal recessive disease caused by variants in the Solute Carrier Family 4 Member 4(SLC4A4) gene. The patients present with metabolic acidosis and low plasma bicarbonate concentration (3~17 mmol/L). In addition, They are often accompanied by ocular abnormalities, intellectual disability and growth retardation. The patient underwent whole exome sequencing and bioinformatics analysis of variant pathogenicity in this study. Then, the minigene assay was used to analyze the splicing site variant further. Compound heterozygous variants in SLC4A4 gene (NM_003759.3), c.145C>T (p.Arg49*) and c.1499+1G>A, were detected by whole exome sequencing. The minigene assay showed a mRNA splicing aberration caused by the c.1499+1G>A variant. Compared with the wild type, the mutant type caused 4-base insertion between exon 10 and 11 of SLC4A4 after expression in HEK293 cells. In conclusion, c.1499+1G>A variant in the SLC4A4 gene may be one of the genetic causes of the patient. Moreover, our study provides the foundation for future gene therapy of such pathogenic variants.